Introduction to toxicogenomics and example case studies - Afshari, Cindy (Henry Stewart Talks, 2009)
What is toxicogenomics and what is it not?, General considerations, Compound discrimination, Pathway modeling, Modulation of the notch pathway, Altered transcripts, Understand compound mechanism of action, Case study: hepatotoxicity, For the future: translation